2008
DOI: 10.1088/0022-3727/42/1/015211
|View full text |Cite
|
Sign up to set email alerts
|

Speed of streamers in argon over a flat surface of a dielectric

Abstract: A pin–pin electrode geometry was used to study the velocities of streamers propagating over a flat dielectric surface and in gas close to the dielectric. The experiments were done in an argon atmosphere, at pressures from 0.1 to 1 bar, with repetitive voltage pulses. The dielectric surface played a noticeable role in discharge ignition and propagation. The average speed of the discharge decreased with higher pressure and lower voltage pulse rise rate. It was higher when the conductive channel between the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 20 publications
11
60
0
Order By: Relevance
“…This fact in itself suggests that the time allowed to the AC discharge to develop (10 to 50 ms in our case) is several orders of magnitude larger than the typical times associated with pulsed breakdown, in 10-100 ns order of magnitude. One typical result for pulsed breakdown is that the breakdown voltage decreases as the voltage ramp decreases [12,13], which suggests a significant overvoltage during the pulsed breakdown process. The overvoltage occurs simply because the voltage rises too quickly (the pulses used are very narrow), and at typical discharge growth speeds of 10 5 to 10 6 m/s [11,12], the discharge grows too slowly to fully form before a significant overvoltage occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact in itself suggests that the time allowed to the AC discharge to develop (10 to 50 ms in our case) is several orders of magnitude larger than the typical times associated with pulsed breakdown, in 10-100 ns order of magnitude. One typical result for pulsed breakdown is that the breakdown voltage decreases as the voltage ramp decreases [12,13], which suggests a significant overvoltage during the pulsed breakdown process. The overvoltage occurs simply because the voltage rises too quickly (the pulses used are very narrow), and at typical discharge growth speeds of 10 5 to 10 6 m/s [11,12], the discharge grows too slowly to fully form before a significant overvoltage occurs.…”
Section: Discussionmentioning
confidence: 99%
“…One typical result for pulsed breakdown is that the breakdown voltage decreases as the voltage ramp decreases [12,13], which suggests a significant overvoltage during the pulsed breakdown process. The overvoltage occurs simply because the voltage rises too quickly (the pulses used are very narrow), and at typical discharge growth speeds of 10 5 to 10 6 m/s [11,12], the discharge grows too slowly to fully form before a significant overvoltage occurs. In the case of AC breakdown, there is no significant overvoltage caused by the formation time because of the very slow ramp of the voltage amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…In surface dielectric barrier discharges in air, Gibalov and Pietsch [2000] have shown that when ε r decreases from 9.8 to 2.4 the surface dielectric barrier discharge propagates farther on the surface. In the work of Sobota et al [2009] in Argon, for ε r varying between 2.3 − 4.5 and 9.1, a very small influence of the surface discharge velocity is observed. Babaeva et al [Babaeva et al, 2006;Babaeva and Kushner , 2009] studied the influence of dielectric dust particles on the discharge structure in air at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 94%
“…It is important to note that in all these studies, the discharge is generated in a point-to-plane geometry and the dielectric is a plane or a cylinder set on one side of the discharge. Recently a pin-pin electrode geometry has been used by Sobota et al [2009] in pure Argon to study the discharge propagation over a flat dielectric surface and in the gas close to the dielectric. These authors also concluded that the discharge propagates faster over the dielectric surface than through the gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation